(untitled) (Texas Journal of Multidisciplinary Studies, 2021)
Saffron (Crocus sativus L.) is an autumnal flowering geophyte whose dried stigmas, well known for their aromatic and coloring power, have been used since immemorial time as a spice in human nutrition, for medicinal purposes and as a dye. Many doubts remain on its origin; it was probably selected and domesticated in Crete during the Late Bronze Age. It has a reverse biological cycle compared with the majority of cultivated and spontaneous plants: flowering first in October-November, then vegetative development until May, which means that the vegetative development is not directly important for production of stigmas, but for the production of new corms. It is a representing an alternative viable crop for sustainable agriculture. Here we review the main biological, genetic and ecological traits associated with agronomic management techniques of saffron in relation to environmental conditions.